Evaluation of the effect of education expenditure policies on income inequality in the Junin, Pasco and Huanuco regions - Villamonte Blas, Ricardo N. (2021)
Perú has had an acceptable economic growth in relation to other Latin American countries in the last 10 years. Even though people's income inequality has been reduced in the 2007-2017 period, it is interesting to analyze the effect of educational policies on income inequality in the regions of: Pasco, Junín and Huánuco, classified regions among those with the lowest personal income in Perú.In the last 10 years, the government has been perfecting the mechanisms for access to public education and improving its public policies, providing a larger budget in order to achieve an increase in educational accessibility.The objective of this study is to carry out an analysis of the effect on income inequality, measured by the Gini coefficient, of a set of representative explanatory variables of educational policies through a proposed panel data econometric model, after a review of specialized literature on the subject and of the main educational policies in the period 2007-2017. The working hypothesis affirms that educational policies had a low impact on reducing income inequalities, the same that was verified through of this investigation.